Refugees at Home: Reading Northern Muslim Experiences through Literary and Cinematic Narratives - Nuha, A. M. F. I.; Thiruvarangan, M. (Faculty of Arts University of Jaffna, Sri Lanka, 2025)
The question of Muslims within the larger discourse on war, displacement, and post-war recovery in Sri Lanka remains largely side-lined, overshadowed by the dominant narratives of Sinhala state victimhood and Tamil nationalist claims and resistance. Despite their mass expulsion from the Northern Province by the LTTE in 1990 and their prolonged displacement, Northern Muslims have often been rendered invisible in both state-sponsored reconciliation processes and Tamil nationalist memory. This study seeks to redress this erasure by examining how Northern Muslim experiences are represented and negotiated through literary and cultural productions that bear witness to their histories of dispossession, survival and return. By analysing Mullai Mushrifa’s poetry collection Iruthalukkana Azhaippu, Vaasu Murugavel’s novel Jaffna Bakery, and Sumathy Sivamohan’s film Amid the Villus, the study seeks to explore how these texts function as counter-narratives to dominant Sinhala and Tamil nationalist discourses that have historically rendered Muslim experiences invisible or politically inconvenient. In addition to literary and cultural productions, this paper also uses oral histories, socio-political doc uments, reports and media coverage for broader contextualization. Grounded in postcolonial theory, nationalism studies, and feminist critique, the objective is to unpack the ways in which these cultural texts mediate questions of identity, home, land, memory, and belonging. The study also seeks to highlight the gendered dimensions of displacement, particularly how Muslim women’s experiences are shaped by intersecting forces of war, nationalism, and patriarchal control. Ultimately, this dissertation aims to demonstrate how literary and cultural forms not only document the trauma of displacement but also serve as spaces of resistance, memory, and reimagination, demanding a more inclusive framework for post-war reconciliation, historical justice, and the rethinking of nationhood in Sri Lanka.
Keywords: Belonging; Displacement; Home; Identity; Nationalism; Northern Muslims; Resettlement